Association of extraintestinal manifestations and anaemia with disease outcomes in patients with inflammatory bowel disease. (2nd July 2016) - Vegh, Zsuzsanna; Kurti, Zsuzsanna; Gonczi, Lorant; Golovics, Petra Anna; Lovasz, Barbara Dorottya; Szita, Istvan; Balogh, Mihaly; Pandur, Tunde; Vavricka, Stephan R; Rogler, Gerhard; Lakatos, Laszlo; Lakatos, Peter Laszlo
Abstract: Objective: The association between extraintestinal manifestations (EIMs) and disease activity suggest a common pathogenetic link with inflammatory bowel disease (IBD). We report on the association of EIMs and anaemia with long-term disease outcomes, including treatment steps, hospitalization, and surgery in the prospective population-based IBD inception cohort from Veszprem province. Methods: Data of 678 incident IBD patients (Crohn's disease/ulcerative colitis(CD/UC): 331/347) diagnosed from 1st January 2000 to 31st December 2012 were analyzed (CD: m/f: 176/155, median age at diagnosis: 28, IQR: 21–40 years, disease duration: 6, IQR: 2–9 years; UC: m/f: 200/147, median age at diagnosis: 36, IQR: 26–50 years, duration: 7, IQR: 4–10 years). Results: EIMs were present in 30% of the CD and 17.3% of the UC patients. In CD, female gender ( p  = 0.02) need for steroid ( p   < 0.001) and azathioprine (AZA) ( p  = 0.02), while in UC, young age at onset ( p  = 0.03), extensive disease ( p  = 0.003), female gender ( p  = 0.07), need for steroids ( p  < 0.001) and AZA ( p  = 0.004) and need for IBD-related hospitalization ( p  = 0.01) were associated with the presence of EIMs. Anaemia was present in 56.7% of the CD and 30.2% of the UC patients. In both CD and UC anaemia was associated with age at onset ( p CD  = 0.001, p UC  = 0.04), disease location/extent ( p CD  = 0.02, p UC  < 0.001), steroid and AZA use (for both p CD, UC  < 0.001), need for surgery/colectomy ( p CD  < 0.001, p UC  = 0.002) and hospitalization ( p CD  = 0.004, p UC  < 0.001) and in CD, it was associated with anti TNF therapy( p  = 0.002). Conclusions: The presence of EIMs was associated with disease phenotype in UC and with treatment strategy in both CD and UC. Additionally, anaemia was associated with hospitalization and surgery in both CD and UC, suggesting that EIMs and anaemia may be helpful in stratifying disease severity in IBD.